Adverse events of vaccines and the consequences of non-vaccination: a critical review - Luana Raposo de Melo Moraes Aps; Marco Aurélio Floriano Piantola; Sara Araujo Pereira; Julia Tavares de Castro; Fernanda Ayane de Oliveira Santos; Luís Carlos de Souza Ferreira (Universidade de São Paulo, 2018)
ABSTRACT OBJECTIVE: To analyze the risks related to vaccines and the impacts of non-vaccination on the world population. METHODS: This is a narrative review that has considered information present in the bibliographic databases NCBI-PubMed, Medline, Lilacs, and Scientific Electronic Library Online (SciELO), between November 2015 and November 2016. For the analysis of outbreaks caused by non-vaccination, we considered the work published between 2010 and 2016. RESULTS: We have described the main components of the vaccines offered by the Brazilian public health system and the adverse events associated with these elements. Except for local inflammatory reactions and rare events, such as exacerbation of autoimmune diseases and allergies, no causal relationship has been demonstrated between the administration of vaccines and autism, Alzheimer's disease, or narcolepsy. On the other hand, the lack of information and the dissemination of non-scientific information have contributed to the reemergence of infectious diseases in several countries in the world and they jeopardize global plans for the eradication of these diseases. CONCLUSIONS: The population should be well informed about the benefits of vaccination and health professionals should assume the role of disseminating truthful information with scientific support on the subject, as an ethical and professional commitment to society.